School Leaders in School Organization: Entrepreneurial Leadership? - Kasim, Norhisham Mohd; Hassan, Salwati; Yaacob, Mohd Rafi; Nordin, Mohd Norazmi; Aida, Noor; Akim, Tumisah; Abbas, Mohd Saleh (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this paper is to present and discuss the model of entrepreneurial leadership in school organizational context and why this style of leadership is importance toward school leaders in school organization. The empirical studies revealed that entrepreneurial leadership positively and significantly have an effect on performance of leaders. Therefore, this conceptual paper introduces the significance of entrepreneurial leadership on school leaders in school organization.